An evaluation of the association of leukopenia and severe infection in patients with systemic lupus erythematosus - Kamoltip Lertchaisataporn (2018)
Background: Leukopenia is a common finding in systemic lupus erythematosus (SLE) and may contribute to severe infections. Objectives: The objectives of this study were to determine the prevalence of leukopenia in SLE patients and examine the association between these conditions and severe infections noting the risk factor of severe infections. Methods: This study was a prospective inception lupus cohort of newly diagnosed SLE patients seen between May 2007 and June 2011. Only cases that had been observed for a minimum of 1 year or died during the study were included. Results: There were 89 SLE patients (92% females), with their mean (SD) age and disease duration at the study entry of 31.7 (12.2) years and 2.4 (2.9) months. Leukopenia was found at the diagnosis in 51.6% of the cases. The cumulative prevalence of leukopenia, lymphopenia, and neutropenia was observed in 57.3%, 96.6%, and 60.7%, respectively. Persistent lymphopenia, noted continuously for more than or equal to 75% of the observation period, was found in 41.6%, but there was no persistent neutropenia. The incidence rate of severe infection was 12.4 per 100 patient-years. There was no difference of severe infection-free survival rate between patients who ever and never had leukopenia. In the multivariate analysis, using cyclophosphamide was the independent predictor for severe infection in SLE (hazard ratio, 2.73; 95% confidence interval, 1.10-6.77). Conclusions: Leukopenia was common in SLE but usually not persistent. In this study, the presence of leukopenia at any time was not the risk factor for severe infection in SLE. Cyclophosphamide was the important predictor for severe infection in SLE. Copyright © 2013 by Lippincott Williams & Wilkins.